Confiabilidade dos parâmetros monitorados em águas por sonda multiparâmetros - Mendonça, Angela Maria (2016)
Concern over water quality in Brazil is being hotly debated currently. In order to obtain information about the water quality at the national level, it was created the National Program for Assessment of Water Quality (PNQA). This program is the main axis of the National Network for Water Quality Monitoring (RNQA). To obtain water quality data and to create a standardized procedure, multiparameter probes were delivered to the federations, which allow determining the quality in real time through a few parameters. The multiparameter probes are presented in the market to supply the basics requirements to determine water quality with standardization, and the cost for the adoption of these probes will depend on the parameters. The more parameters evaluated, the higher its cost and it can derail monitoring. The basic probes simultaneously evaluate parameters such as dissolved oxygen, conductivity, total suspended solids, redox potential, temperature, pH and turbidity. These parameters allow inferences about the water quality and it has the advantage of providing results within minutes. However, the results are reliable? In this context, the aim of this thesis was to evaluate the reliability of the data presented by the multiparameter probe for monitoring of surface water, which was determined and compared to the results presented by multiparameter probe mark Aquaread AP 1000 with used equipment and methodologies by traditional laboratories. The time of immersion of the probe was determined for all its parameters were stabilized, the transport time so that did not occur changes in the sample values determined in field, we compared their readings with traditional methods and created a protocol probe operation. The results presented in research showed that the average time recommended for stabilization of parameters is 20 minutes. Regarding the conservation of water samples collected in the field, there was no significant difference in the readings over time. The multiparameter probe showed no reliable values in order to assert the water quality due to a high discrepancy between individual equipment, laboratory analysis regarding the probe, being a correction of each parameter required.